Stressors-induced cognitive dysfunction during aging: mechanisms and future challenges - Zhang, Yizhe; Zhang, Xiao; Guo, Jiaxi; Dai, Wanbing; Chen, Sifan; Huang, Lili; Xiang, Xuwu; Yu, Weifeng; Su, Diansan (Frontiers in Aging Neuroscience, 2025)
Stressful events can lead to transient impairments in learning and memory, a phenomenon more pronounced in the elderly. As global life expectancy rises, the shift toward an aging society underscores the urgent need for effective preventive strategies against stress-induced cognitive dysfunction. Elucidating its pathogenesis is essential for developing neuroprotective interventions and mitigating medical and societal impacts. In this study, male C57BL/6 mice aged 2 and 18 months were subjected to restraint stress (2 h/day for 14 days). Spontaneous activity and anxiety-like behavior were evaluated using the open field test, and cognitive performance was assessed via the novel object recognition test. mRNA sequencing revealed differentially expressed genes, which were further analyzed using Gene Ontology enrichment through the Database for Annotation, Visualization and Integrated Discovery (DAVID) database. Key molecular findings were validated by Quantitative Polymerase Chain Reaction (RT-qPCR), Western blot, and immunofluorescence. Additionally, a literature review was conducted to identify emerging research directions. Our results reveal that aged mice exhibit impaired upregulation of protective Endoplasmic Reticulum (ER) stress genes and show downregulation of mitochondrial expression and translation pathways, in contrast to young mice in which stress primarily upregulated genes involved in mitochondrial organization and Adenosine Triphosphate (ATP) metabolism. These age-specific vulnerabilities highlight ER stress and mitochondrial dysfunction as potential intervention targets.